Diseño curricular de la cátedra itinerante sobre la vida y obra de Pedro Vicente Maldonado, octavo EGB, Distrito Riobamba-Chambo - Naranjo Yancha, Mauricio David (2023)
The present research project was carried out with the purpose of determining the curricular design of the itinerant chair on the life and work of Pedro Vicente Maldonado, eighth EGB, Riobamba district, the research focuses on knowing the student's knowledge and the teacher's preparation for teach this type of lectures that are important in the education process, since the lack of interest of the new generations in the historical, patriotic and civic legacy of the different historical figures is evident, being replaced by other types of topics and learning that do not have a significant value in the knowledge of the student. The need to investigate arises from the central problem that is due to the ignorance of the majority of students about the life of Pedro Vicente Maldonado in institutions both in rural and urban areas. A qualitative methodology was used for the investigation and obtaining of numerical data and the statistical process, a documentary modality for the series of bibliographic documents, a field study for the collection of information, the historical use for the analysis and revision of the information. of relevant facts about Maldonado and the eighth grade Social Studies curriculum. The survey for students and teachers was used, which served to verify and verify the existing problem and based on this, reach the conclusions about the ignorance of the information of the illustrious Riobambeño and that teachers do not apply innovative strategies, they do not self-train by teach this type of subject that is not within the current curriculum.